2011
DOI: 10.1055/s-0031-1284369
|View full text |Cite
|
Sign up to set email alerts
|

Low Prevalence of Clinically High-Risk Women and Pathological Thyroid Ultrasound among Pregnant Women Positive in Universal Screening for Thyroid Disorders

Abstract: Less than half of the positively screened pregnant women can be classified as high-risk and almost half of them had not autoimmune pattern in TUS. High- and low-risk pregnant women have similar clinical and laboratory characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Finding of five articles showed that case-finding screening would miss between 30 and 55 % of pregnant women with thyroid dysfunction [18][19][20][21][22] and only one study did not support the feasibility of universal screening in pregnant women [23]. All studies showed that the prevalence of thyroid dysfunction (especially hypothyroidism) was higher in the group of pregnant women with risk factors for thyroid disease.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finding of five articles showed that case-finding screening would miss between 30 and 55 % of pregnant women with thyroid dysfunction [18][19][20][21][22] and only one study did not support the feasibility of universal screening in pregnant women [23]. All studies showed that the prevalence of thyroid dysfunction (especially hypothyroidism) was higher in the group of pregnant women with risk factors for thyroid disease.…”
Section: Resultsmentioning
confidence: 99%
“…One study on universal screening showed that less than half of the women with positive pregnancy tests could be classified as high risk [23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the American Endocrine Society guidelines some members recommended screening while others did not [9]. All current recommendations support a targeted screening strategy, but such a strategy may miss at least from 33 to 81% of women with hypothyroidism [97,98,99,100]. …”
Section: Screening For Thyroid Hypofunction In Pregnancymentioning
confidence: 99%
“…However, the only prospective randomized trial undertaken to assess the value of screening in relation to childhood cognitive functional outcome failed to show any benefit of screening in pregnancy [88]. Nevertheless, there is support for screening to prevent pregnancy-associated problems [29,99,101] in addition to recognition of post-partum thyroiditis [102]. Despite finding no significant decrease in obstetric complications with universal screening and case finding, Negro et al [69] showed fewer obstetric complications in the low risk group identified by universal screening and benefiting from hypo/hyperthyroidism treatment.…”
Section: Screening For Thyroid Hypofunction In Pregnancymentioning
confidence: 99%